2011
DOI: 10.1142/s0219519411004253
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Functional Electrical Stimulation for Correction of Foot Drop: A Comparison Between Subacute and Chronic Stroke Patients

Abstract: Functional electrical stimulation (FES) allows active exercises for correction of foot drop in stroke patients. Our objective is to evaluate and compare the effects of FES therapy in walking ability, calf muscle spasticity, and lower-extremity motor recovery between subacute and chronic stroke patients. Twenty consecutive hemiplegic patients having foot drop were assigned either to subacute or chronic group. Both group subjects were treated with conventional rehabilitation program combined with FES therapy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A thorough review on earlier FES systems to correct DF since the 1960s up to 2001 can be found elsewhere [12]. Functional electrical stimulation as a rehabilitation tool has been reported to improve gait when combined with conventional therapies [13][14][15][16][17], however it is not going to be addressed as a main topic, since it falls outside the scope of this article. Nonetheless, therapeutic effects of FES may be brought to discussion when necessary.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review on earlier FES systems to correct DF since the 1960s up to 2001 can be found elsewhere [12]. Functional electrical stimulation as a rehabilitation tool has been reported to improve gait when combined with conventional therapies [13][14][15][16][17], however it is not going to be addressed as a main topic, since it falls outside the scope of this article. Nonetheless, therapeutic effects of FES may be brought to discussion when necessary.…”
Section: Introductionmentioning
confidence: 99%